(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This article focuses on thematic structure, genre, characterization, and literary devices of "Jane Eyre" by Charlotte Brontë and " O’tkan kunlar" by Abdulla Qodiriy to explore how both novels portray love, social inequality, and personal struggle. Although written in different cultural contexts—Victorian England and 19th-century Central Asia—the novels share universal concerns about morality, independence, and social expectations. Special attention is given to the role of women in society and the extent to which this theme aligns with each work’s main message. The findings show that both novels use strong female characters to critique restrictive societal norms, making the theme of women’s role crucial to both narratives.